Website-Based Guest Book Application for Al Hidayah Recitation in Purwosari Village - Rizkysari Meimaharani; Hanik Hidayati; Esti Wijayanti (Jurnal Info Sains : Informatika dan Sains, 2023)
The website-based guestbook application for Al Hidayah recitation is a system designed to memorization and simplify the process of managing visits of recitation participants. With this application, this process can be done online via the website. This guestbook application was developed using web technologies such as HTML, CSS and Java Script. Apart from that, using a database uses visit data storage efficiently and safely. With this application, it is hoped that study participants can easily access and register for visits practically and efficiently.